2017
DOI: 10.1080/00220620.2017.1399864
|View full text |Cite
|
Sign up to set email alerts
|

Professionalism and competing responsibilities: moderating competitive performativity in school autonomy reform

Abstract: Discourses promoting the benefits of school autonomy have floated freely internationally since moves in the 1980s to greater devolution in the UK, New Zealand, the USA, Australia and Sweden. The most recent Australian version, Independent Public Schools (IPS), grants school leaders more latitude over aspects of their work. But this autonomy is constrained by technologies of competitive performativity, now the norm across Australian and other school systems. Entrepreneurial policies focused on competition, comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
18
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(18 citation statements)
references
References 43 publications
0
18
0
Order By: Relevance
“…This work identified important issues related to teacher leadership and professionalism. Findings of the three studies provided evidence to support the conclusions of Wong (2017), Cheng, (1996; Gobby et al, (2018); Pearson & Moomaw, (2005) and in that administrator's leadership style and preparation at the central or at the school level is a variable that influences teacher professionalism and leadership. By maintaining a pyramidal leadership style, authorities of the Department of Education, as well as principals and supervisors limited teachers' autonomy and motivation for innovation.…”
Section: Discussionmentioning
confidence: 62%
“…This work identified important issues related to teacher leadership and professionalism. Findings of the three studies provided evidence to support the conclusions of Wong (2017), Cheng, (1996; Gobby et al, (2018); Pearson & Moomaw, (2005) and in that administrator's leadership style and preparation at the central or at the school level is a variable that influences teacher professionalism and leadership. By maintaining a pyramidal leadership style, authorities of the Department of Education, as well as principals and supervisors limited teachers' autonomy and motivation for innovation.…”
Section: Discussionmentioning
confidence: 62%
“…These findings might raise Connell's (2013) and Lindblom's (1995) argument about markets being unequal and generating inequality. However, it could be argued that this "erosion" was minimized through: (1) different state IPS policies and experiences in Western Australia and Queensland; (2) school leaders' actions in these states to promote their school's social goals or to promote teacher professionalism (Gobby et al, 2018;Keddie et al, 2018); and (3) performance pay for teachers, while remaining of interest to governments, continues not to be implemented.…”
Section: Resultsmentioning
confidence: 99%
“…IPSs, discussion about performance pay for teachers, and increased use of commercialization and marketization, however, might be viewed as a move to a democratic deficit. Yet, several Australian studies have highlighted school leaders' understanding of these impacts and the ways in which some school leaders have sought to ameliorate them by promoting moral and professional responsibilities, particularly in relation to IPSs (Cranston, 2013;Ehrich, Harris, Klenowski, Smeed, & Ainscow, 2015;Gobby, Keddie, & Blackmore, 2018;Keddie, 2014;Keddie, Gobby, & Wilkinson, 2018;Kimber & Ehrich, 2011). These actions may illustrate that adherence to social justice has "moderated" this move to a "democratic deficit" (Kimber & Ehrich, 2011;Kimber & Maddox, 2003).…”
mentioning
confidence: 99%
“…For example, some studies have found that distributed leadership hurts teacher professionalism, possibly under the assumption that they can perceive an increase in their functions without necessarily being reflected in an increase in their authority (Joo, 2020). However, some elements of distributed leadership, such as collegial work and collaboration among teachers have also been seen to have a positive effect on teacher professionalism (Gobby et al, 2018;Wiyono & Triwiyanto, 2018), mostly because it has an effect that improves trust in their co-workers.…”
Section: Literature Reviewmentioning
confidence: 99%
“…1996);Gobby et al, (2018);Pearson & Moomaw, (2005) andSterrett, (2015) in that administrator's leadership style and preparation at the central or at the school level is a variable that influences teacher professionalism and leadership. By maintaining a pyramidal leadership style, authorities of the Department of Education, as well as principals and supervisors limited teachers' autonomy and motivation for innovation.…”
mentioning
confidence: 99%